SIZING OPTIMIZATION OF STANDALONE PHOTOVOLTAIC SYSTEM FOR RESIDENTIAL LIGHTING - AL RIZA, DIMAS FIRMANDA (2011)
This study presents a sizing methodology to optimize photovoltaic array and battery storage in a standalone photovoltaic (PV) system with lighting load. Sizing using the deterministic method was carried out for initial design. Stochastic method by mean of Loss of Power Supply Probability (LPSP) calculation was developed using daily weather data input. The weather data consists of ambient temperature, relative humidity and solar radiation. An estimation method of hourly solar radiation data is also developed in this study to complete any missing solar radiation data in the dataset. Then, complete time-series dataset can be used for LPSP calculation and system simulation. Size optimization was carried out using a graphical method. System size was optimized based on desired system performance (indicated by LPSP value) and minimum cost that consist of Capital Cost and Life-cycle cost. In addition, Excess energy value is used as over-design indicator. A comparison of sizing optimization methods was carried out, and it was found that the design space approach giving flexibility in the selection of PV panel and battery capacity compared to other methods. The sizing result of this method is a configuration of 500Wp PV array and 400Ah battery. Economic analyses, including cost of the energy and payback period for selected configuration are studied. A simulation model was developed using TRNSYS 16 to test the sizing results. Experimental data was used to validate the simulation results. Simulation validation shows that result accuracy has improved. The results indicated that Root Mean Square Error (RMSE) between simulated and measured battery voltage has decreased by 50% compared to previous work. The validated simulation model then was used to test and analyse the selected PV system configuration.